A Point Prevalence Study of the Use of Antibiotics in Six Tertiary Care Hospitals in the Kathmandu Valley, Nepal - Jha, N.; Thapa, B.; Pathak, S. B.; Pandey, A.; Pokhrel, S.; Shankar, P. R.; Bhandary, S.; Mudvari, A.; Dangal, G. (Kathmandu University Medical Journal, 2022)
Background Point prevalence survey (PPS) on antibiotic use developed by the WHO has already been used in many hospitals globally. Objective To obtain information on antibiotic prescription using point prevalence survey methodology in six private hospitals in the Kathmandu valley. Method This descriptive cross-sectional study was completed during 20th July to 28th July 2021 using point prevalence survey methodology. The study was conducted among inpatients admitted at or before 8:00 AM on the day of survey in various wards. Data was presented as frequencies and percentages. Result Maximum number of patients were above 60 years [34 (18.7%)]. Number of male and female participants were equal [91 (50%)]. Only one antibiotic was used in 81 patients (44.5%) followed by two antibiotics in 71 (39%) patients. Duration of prophylactic antibiotic use was one day in 66 (63.7%) patients. Blood, urine, sputum, and wound swabs were the common samples for culture. Cultures were positive for 17 (24.7%) samples. The common organisms isolated were E. Coli, Pseudomonas aeruginosa and Klebsiella pneumoniae. Ceftriaxone was the most used antibiotic. Drug and therapeutics, infection control committee and pharmacovigilance activities were present in 3/6 (50%) study sites. Antimicrobial stewardship was present in 3/6 (50%) and microbiological services was present in all hospitals. Antibiotic formulary and antibiotic guideline were present in 4/6 sites and facilities to audit or review surgical antibiotic prophylaxis choice in 2/6 (33.3%) sites, facility to monitor antibiotic use in 4/6 (66.6%) and cumulative antibiotic susceptibility reports in 2/6 (33.3%) study sites. Conclusion Ceftriaxone was the most used antibiotic. E. Coli, Pseudomonas aeruginosa and Klebsiella pneumonia were the commonly isolated organisms. Not all parameters for infrastructure, policy and practice and monitoring and feedback were present at the study sites.